Analisis Keterampilan Memberi Penguatan dalam Meningkatkan Efektivitas Pembelajaran Anak Usia Dini - Yunita Sari Nasution; Kholidah Nur; Nurmaliana Harahap; Nur Hikmah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to analyze the skills of providing learning variations to increase the effectiveness of the learning process in early childhood. Early childhood is in a very dynamic development phase, where monotonous teaching methods can hinder their attention and motivation. Therefore, the use of variations in teaching methods, such as changes in activity types, duration, learning media, and interactive approaches, can have a positive impact on children's involvement in learning activities. This research uses a qualitative approach with a literature study method that examines various sources related to variations in learning and their impact on early childhood development. The results of the analysis show that a variety of learning activities can increase children's motivation, prolong concentration, support multisensory learning, and develop children's social and emotional skills. Learning that involves various methods and media allows children to learn through direct experience thereby strengthening their understanding of the concepts being taught. This research concludes that the skill of providing variety in learning not only increases learning effectiveness, but also contributes to children's holistic development. Therefore, it is important for educators to master these skills and apply them consistently in early childhood learning activities.